Viral infection-induced changes in the expression profile of non-RLR DExD/H-box RNA helicases (DDX1, DDX3, DHX9, DDX21 and DHX36) in zebrafish and common carp. Issue 104 (September 2020) - Mojzesz, Miriam; Klak, Katarzyna; Wojtal, Paulina; Adamek, Mikolaj; Podlasz, Piotr; Chmielewska-Krzesinska, Malgorzata; Matras, Marek; Reichert, Michal; Chadzinska, Magdalena; Rakus, Krzysztof
Abstract: In mammals, several non-RLR DExD/H-box RNA helicases are involve in sensing of viral nucleic acids and activation of antiviral immune response, however their role in the immune defense of fish is much less known. In this study, the expression profile of non-RLR DExD/H-box RNA helicase genes: ddx1, ddx3, dhx9, ddx21 and dhx36, was studied in zebrafish ( Danio rerio ) and common carp ( Cyprinus carpio L.) during infection with two RNA viruses: spring viremia of carp virus (SVCV) and Chum salmon reovirus (CSV). Bioinformatic analysis of the amino acid sequences of the core helicase of DDX1, DDX3, DHX9, DDX21 and DHX36 in zebrafish and common carp revealed presence of all conserved motifs found amongst all other species, with the exception of common carp DHX9 which do not possess motif V. The transcripts of studied DExD/H-box RNA helicases were found in zebrafish ZF4 cell line as well as in all studied organs from zebrafish and common carp. The expression study demonstrated the up-regulation of the expression of selected non-RLR DExD/H-box RNA helicases during viral infections in ZF4 cell line ( in vitro study) and in zebrafish and common carp organs ( in vivo study). DDX1 was the only DExD/H-box RNA helicase which expression was repetitively up-regulated during in vivo infections with SVCV and CSV in zebrafish and SVCV in common carp. In ZF4 cells and kidney of common carp, viral infection-induced up-regulation of DExD/H-box RNA helicases preceded the up-regulation of type I IFN gene. Our results suggest that studied non-RLR DExD/H-box RNA helicases might be involved in antiviral immune response in fish. Highlights: Expression of non-RLR RNA helicases is up-regulated upon viral infection in fish. Their up-regulation preceded the up-regulation of type I IFN gene expression. DDX1 is up-regulated during infection with both SVCV and CSV in zebrafish and carp.